Analisis Manajemen Risiko Aset Teknologi Informasi pada Perusahaan Sistem Integrator dengan Menggunakan Metode Octave Allegro - Amelia Dwi Indriani; Tristyanti Yunitasari (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2025)
The Utilization of Information Technology frequently carries significant security risks, both from external threats such as cyber attacks (viruses, malware, phishing, ransomware) and from internal factors such as human error. This research aims to identify, assess, and mitigate the risks of information technology assets in an Indonesian system integrator company using the OCTAVE Allegro method. This method was chosen because it focuses on critical information assets and provides a structured approach through eight steps in four phases of analysis. The results of the study show that there are four critical assets in the company's information technology, namely hardware, software, data and information, as well as access rights and credentials. Based on the risk assessment matrix, data and information assets have the highest risk score with an average of 38.8, followed by access rights and credentials (38), software (37.42), and hardware (36.33). All risk categories are in POOL 1, which means they require immediate mitigation measures. Consistent implementation of risk management is expected to strengthen the company's resilience to information security threats and also enhance its reputation and competitiveness in the technology industry.